Exploration of Hi-Res Sikap: Patriarchal Attitude and Support for Militaristic Government in Indonesia - Hardi, Lalu Ary Kurniawan; Maritta, Alifia Moci (Indonesian Journal of Political Studies, 2026)
This study investigates whether patriarchal attitudes predict public support for a militaristic government in Indonesia amid concerns about democratic backsliding and renewed military influence in civilian politics. Drawing on nationally distributed survey data from the 2025 HI-RES SIKAP project (N ≈ 2,500), the analysis examines whether agreement with the belief that men are better political leaders than women is associated with stronger endorsement of military rule when civilian institutions are perceived as ineffective. Using ordinary least squares regression with sequential model specifications, the study controls for nationalism, trust in religious leaders, education, income, sex, religiosity, support for democracy, tolerance for electoral violence, and presidential preference. The findings demonstrate that patriarchal attitude is a robust and statistically significant predictor of support for militaristic governance across all models. Interaction analysis further reveals that the effect is particularly pronounced among female respondents. Overall, the results underscore the central role of gender ideology in shaping orientations toward authority, hierarchy, and coercive political order.